Measuring epidermal effects of ostomy skin barriers. Issue 2 (2nd November 2018) - Grove, Gary; Houser, Tim; Sibbald, Gary; Salvadalena, Ginger
Abstract: Background: Ostomy barriers are adhesive devices designed to hold pouching systems to the abdomen and protect the peristomal skin from stoma effluent. The objective of this study was to determine differences in the extent of skin trauma resulting from serially applying and removing two types of ostomy barriers. Methods: The study was a randomized, prospective, repeated measure trial involving healthy volunteers. The ostomy skin barriers were applied to the abdomen and changed every 3‐4 days over a 17‐day period. Skin observations (erythema, stripping, edge irritation and overall comparisons) were completed by a trained (blinded) observer. Transepidermal water loss (TEWL) measurements were completed by a separate (blinded) technician. TEWL was measured in a designated site and again in the most visually traumatized location at termination. Results: Statistically significant differences were found between the two test devices in all assessments but visual observation of erythema. Highly significant differences in TEWL were found between the test products when measured at termination from the most visually traumatized sites. Conclusions: The ostomy barrier with ceramide was significantly less disruptive to the epidermis than the ostomy barrier without ceramide. TEWL measurements were more sensitive to changes in the barrier function of the skin than visual observation of erythema.